2019
DOI: 10.14569/ijacsa.2019.0101066
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Full Immersion Techniques for Enhancing Workers Performance, 20 years Later: A Review and a Reformulation

Abstract: The principal aim of this article is to review and reformulate the work published by Alfaro-Casas, Bridi and Fialho [1], in 1997, about the use of virtual reality immersion techniques for enhancing workers performance'. The challenge to be solved is related to the discussion about eventual advances occurring since the publication of the original work published. The strength of the achievements relies on the open dialogue established with different human cognition theories. We consider not only Humberto Maturan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…As a result of utilizing a cost-effective smartphone-based VR system for classroom teaching, it is suggested to use VR for leading immersion and realistic learning [6]. An example of an evaluation study is a review of the author's work of 20 years ago that confirmed that achieving experience through VR has a positive impact on worker performance [7].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of utilizing a cost-effective smartphone-based VR system for classroom teaching, it is suggested to use VR for leading immersion and realistic learning [6]. An example of an evaluation study is a review of the author's work of 20 years ago that confirmed that achieving experience through VR has a positive impact on worker performance [7].…”
Section: Related Workmentioning
confidence: 99%
“…For tactile senses, haptic devices such as PHANToM OMNI 1 , PHANToM Desktop 2 , or Novint Falcon 3 are used. www.ijacsa.thesai.org Basically, this experimental system is implemented C++ language software development environment, in addition to open software tools, such as UNITY Engine 4 , CHAI3D 5 , OpenGL 6 , and OpenHaptics Toolkit 7 . UNITY Engine is a cross-platform game engine for producing content such as 3D video games, architectural visualization, and real-time 3D animation, and it provides functions that are easy to produce for Oculus Rift device programs.…”
Section: A Implementation Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The final users of the application can be people not familiar with technologies, and for them it is necessary to reduce the complexity of the model. Finally, the different topics covered should be considered for teaching applications, considering the diversity of learner profiles, as well as the learning and thinking styles [4], and the potential of the different hardware and software elements to be used for different types of applications, considering also the costs and technological feasibility for the implementation of these systems, which will undoubtedly contribute in an important way to the teaching/learning activities, and also considering the open problems of immersive technologies.…”
Section: Knowledge Construction By Inmersion In Immersive Technolmentioning
confidence: 99%
“…The conception and design of systems to support learning activities, mediated by resources offered by emerging technologies associated with computing, the Web and other sources which incorporate the possibility of adapting activities, learning objects and interaction to the individual profiles and needs of cognoscent subjects [1], [2], [3], is a research topic that has caught the attention of many research groups focusing on the problem, considering different educational philosophies such as: Instructional planning, social-cultural, social learning, the humanist perspective of education, constructivism and constructionism, which notably influenced the architecture and development of these systems during the different stages of development of this important area of research [4], [5].…”
Section: Introductionmentioning
confidence: 99%